Dust layer resistance in the slotted filter - Yulia Aleksandrovna Zykova; Nikolay Mitrofanovich Samokhvalov; Vladimir Vladimirovich Vinogradov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
Relevance of the work. Natural gas produced from wells in the fields, is not a commodity product, as it contains a lot of impurities, including mechanical ones. Therefore, the produced gas is directed to the gas treatment units. One of the stages of the technological cycle is decontamination. Relevance of the research is caused by the need to study the hydraulic resistance of the dust precipitate in the new device for cleaning dusty gases by filtration - slotted filter, which has not been previously studied. The existing methods of calculating the gain of hydraulic resistance are not useful for the dust collecting devices. The main aim of the research is tocarry out the laboratory testing of the slotted filter for identifying the options of precipitate formation and their mathematical description, and development of methodology for calculating a gain of hydraulic resistance when cleaning dusty gases. Research methods are based on the results of physical modeling of dusty gases filteration to determine the gain of hydraulic resistance and on theoretical analysis of the Darcy equation for mechanisms of precipitation and pore clogging with respect to the slotted filter. Results. The paper introduces theoretical calculations based on hydraulic resistance when cleaning dusty gases in the slotted filter for filtering mechanisms with precipitation and pore clogging, derived from Poiseuille equation changes. The authors have considered a comparison of the calculated data with the experimental ones using these equations. It is shown that precipitation mechanism convergence of the calculated and the experimental resistance gain is on the average of 10 % and there was significant deviation over 100 % in pore clogging mechanism convergence. The paper introduces the dependence on calculation of dust layer resistivity, which takes into account the curvature of the channels in the dust layer in contrast to the Ergun and Kozeny-Karman equations. The authors proposed the mathematical model, which takes into account the filtering mechanism to form a precipitate, which is the basis for calculating the hydraulic resistance of the slotted filter. Conclusions. The developed calculation method allows calculating with a reasonable degree of accuracy the hydraulic resistance of the slotted filter considering the characteristics of the filter septum and physical properties of dust and gas, depending on the flow rate, duration of gas and dust cleaning. The technique allows simulating and designing a slotted filter with minimum hydraulic resistance, thereby reducing operating costs.